1998
DOI: 10.1152/ajpheart.1998.274.6.h1928
|View full text |Cite
|
Sign up to set email alerts
|

Stretch force on vascular smooth muscle cells enhances oxidation of LDL via superoxide production

Abstract: Hemodynamic forces on vasculature profoundly influence atherogenesis. We examined the effect of stretch force on the oxidation of low-density lipoprotein (LDL) by rat aortic smooth muscle cells (RASM) and superoxide production. Stretch force was imposed on RASM cultured on deformable dishes by stretching the dishes. Incubation of native LDL with static RASM for 24 h resulted in LDL oxidation as indicated by increases in thiobarbituric acid-reacting substances from 9.5 ± 2.3 to 24.5 ± 2.3 nmol malondialdehyde/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Possibly, this was due to an inadequate amount of tissue. Alternatively, the absence of distending pressure may have played a role, since stretch has been found to enhance ROS production in both endothelium and vascular smooth muscle (2,17). In any case, LDCL and EPR spectroscopy in distal pulmonary arteries provided results consistent with the significant increases in DCF fluorescence caused by hypoxia in myocytes from these vessels (Figs.…”
Section: Discussionmentioning
confidence: 67%
“…Possibly, this was due to an inadequate amount of tissue. Alternatively, the absence of distending pressure may have played a role, since stretch has been found to enhance ROS production in both endothelium and vascular smooth muscle (2,17). In any case, LDCL and EPR spectroscopy in distal pulmonary arteries provided results consistent with the significant increases in DCF fluorescence caused by hypoxia in myocytes from these vessels (Figs.…”
Section: Discussionmentioning
confidence: 67%
“…Meyer et al 15 induced luminal pressures on rabbit aorta in vitro and observed that this stretching increased the uptake of LDL into the arterial wall. More recently, Inoue et al 16 observed that mechanical stretching of cultured smooth muscle cells enhances ox-LDL and superoxide production in the exposed cells. 16 Thus, the combination of increased influx of LDL into the arterial wall and increased oxidative stress may offer a mechanistic explanation of how elevated blood pressure enhances the development of atherosclerosis and ox-LDL.…”
Section: Discussionmentioning
confidence: 99%
“…In injured vessels, vascular stretch affects both the endothelium and vascular smooth muscle. Increased production of ROS in response to cyclic mechanical stretch has been described in endothelial cells (6,104,170,171), vascular smooth muscle cells (62,74,113), fibroblasts (8), and cardiac myocytes (4). Superoxide appears to be the initial species generated in these cell types.…”
Section: Cyclic Stretch and Control Of Ros Productionmentioning
confidence: 99%